Overexpression long non-coding RNA LINC00673 is associated with poor prognosis and promotes invasion and metastasis in tongue squamous cell carcinoma - Yu, Jianjun (Oncotarget, 2016)
Long non-coding RNAs (lncRNAs) associated with the tumorigenesis of human cancers. However, the relevance of lncRNAs in tongue squamous cell carcinoma (TSCC) is still unclear. To discover novel TSCC-related lncRNAs, we analyzed the lncRNA expression patterns in two sets of TSCC gene expression profile data, and found that long intergenic non-coding RNA 673 (LINC00673) was significantly upregulated in TSCC samples. Then we examined LINC00673 expression in 202 TSCC tissue specimens, LINC00673 is highly expressed in a significant proportion of human TSCC biopsies and correlates with poor prognosis. Knockdown LINC00673 significantly inhibited the cell invasion and migration capability in TSCC cells. Our findings suggest that LINC00673 may play an essential role in TSCC progression and might serve as a potential biomarker for early detection and prognosis prediction of TSCC.